2005
DOI: 10.2298/mpns0504147i
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic osteopathy

Abstract: Literature data are contradictory concerning the occurrence of bone fractures in diabetic patients. A survey of bone fracture occurrence in diabetic patients was performed in "Veljko Vlahović Medical Center" in Vrbas and it included a group of 100 patients with diabetic disease. The results show that 12 patients had some fractures: mostly females in postmenopause, aged and with secondary insulin-dependent diabetes and most frequently arm fractures. Considering contradictory literature data, further longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Our findings suggest that vitamin D deficiency is not the cause of diabetic osteopathy in our patients group, although alterations of calcium and Vitamin D3 balance have been implicated as contributing factors of diabetic osteopenia by some but not all authors [47][48][49][50] and even shortly after diagnosis with T1D children presented with decreased lumbar spine BMD and decreased bone formation markers concentration of the carboxy-terminal propeptide of type I collagen [51]. In most studies biochemical parameters of calcium and bone metabolism showed no clear relationship to the bone mineral density measurements [52,53]. From few bone histology studies in humans and experimental studies there is evidence that a decreased bone formation is one major mechanism leading to reduced bone mass in diabetics.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings suggest that vitamin D deficiency is not the cause of diabetic osteopathy in our patients group, although alterations of calcium and Vitamin D3 balance have been implicated as contributing factors of diabetic osteopenia by some but not all authors [47][48][49][50] and even shortly after diagnosis with T1D children presented with decreased lumbar spine BMD and decreased bone formation markers concentration of the carboxy-terminal propeptide of type I collagen [51]. In most studies biochemical parameters of calcium and bone metabolism showed no clear relationship to the bone mineral density measurements [52,53]. From few bone histology studies in humans and experimental studies there is evidence that a decreased bone formation is one major mechanism leading to reduced bone mass in diabetics.…”
Section: Discussionmentioning
confidence: 59%